Late outcome of extracardiac Fontan patients: 32 years of follow-up. (11th May 2022) - Giannico, Salvatore; Trezzi, Matteo; Cantarutti, Nicoletta; Cafiero, Giulia; Ravà, Lucilla; Adorisio, Rachele; Brancaccio, Gianluca; Albanese, Sonia; Drago, Fabrizio; Carotti, Adriano; Amodeo, Antonio; Galletti, Lorenzo
Abstract: OBJECTIVES: We sought to evaluate the long-term survival and risk factors for morbidity and mortality in our cohort of patients after extracardiac (EC) Fontan. METHODS: We collected and analysed follow-up data until September 2020 for all patients who underwent EC Fontan operation at our institution from November 1988 to November 2015. RESULTS: Out of 406 patients treated with EC Fontan at a mean age of 5.4 ± 4.5 years, 372 (91.6%) were discharged home; 15% were lost to follow-up. The median follow-up was 14.6 years (interquartile range 8.7–20.3). Two hundred patients (54%) had a good long-term outcome, with an event-free long-term survival, but late adverse events of any kind needing interventional or surgical reoperations were reported in 128 patients (34%). Forty-four patients (12%) developed late Fontan failure. Thirty-seven survivors (10%) had late arrhythmias, with the need for pacemaker implantation. Obstruction of the cavopulmonary pathway occurred in 49 patients (13%), but just 8 patients needed conduit surgical replacement. At 32 years, the survival probability was 84%. The risk of orthotopic heart transplant, considering death as a competing event (showed as cumulative incidence), was 12.5%. A preoperative diagnosis of hypoplastic left heart syndrome was an independent risk factor for the need for heart transplant. CONCLUSIONS: The EC Fontan shows satisfactory long-term survival and low incidence of adverse events and late failure. Conduit replacement is rare, and its longevity may not represent a substantial issue in these patients. However, as with other technical variants, the need for reoperations during long-term follow-up is a significant challenge. Abstract : The common pathway of treatment for children with a single ventricle is the staged establishment of a series circuit according to the principle of Fontan [1, 2].